Filsafat dan Agama: Pendekatan Rasionalitas dan Spiritualitas - Ahmad Syatori, Syatori (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2024)
Religion and philosophy are two components that direct humans in achieving life goals. It is this fundamental difference that gives rise to the tendency for symmetrical and non-reciprocal development between philosophy and religion in the field of modern "knowledge". The terms philosophy and religion have meanings that are understood by many people in different ways. Philosophy in its operation begins with reason, while religion begins with revelation. Philosophy is a particular field of science that examines how humans can think deeply about something, while religion is a special field of science that examines how humans can behave and behave well based on a teaching that is in accordance with religious guidance. Basically between philosophy and religion have very basic differences, but the difference is not a cause of separation between the two, it can actually be a meeting point in solving a problem and providing solutions and solutions to a particular problem. Philosophy and religion in different positions will certainly produce different sources of knowledge. Where philosophy can find a scientific knowledge rationally, while religion can find a religious knowledge spiritually